DIRECTIONS OF IMPROVEMENT OF ACTIVITY OF HOUSING AND COMMUNAL ENTERPRISES - SMOLINSKA, NATALIA; SOKIL, VOLODYMYR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The purpose of this study is to analyze the theoretical foundations of management and trends in housing and communal services, to develop recommendations for  tariffs formation  for maintenance services of buildings and adjacent areas. To achieve the objectives of the article, the authors used a set of scientific methods that ensure the conceptual integrity of the study, in particular: methods of statistical and comparative analysis, which allowed to assess the dynamics of change in the housing sector objectively; induction, deduction, theoretical generalization to explore foreign experience in the management of housing and communal services; historical and logical - for the study of housing reform; methods of dialectical logic, induction, deduction - to substantiate the strategic directions of development of utilities; comparative and statistical analysis - to study the effectiveness of housing and communal services; economic and mathematical - to improve the tariff payment system for utilities and forecasting individual indicators. The hypothesis is proved that transparency and close interaction with consumers of utility services and improvement of the services tariff will contribute to the efficient operation of utility companies and increase the quality of services provided. The results of this study, considering the world experience and the proposed recommendations, are of interest to housing and communal services, which are trying to strengthen their competitive position in the market by increasing the confidence of their customers and improving the quality of services. The given study contains a description of the main parameters of managing the financial stability of the enterprise by levels of management; reveals the characteristics of modern small restaurant business and the problems that arise during the management of its financial stability; proposals are made to ensure the financial stability of a small enterprise, namely, the proposal is given to pay attention to three main components: the efficiency of use and increase of equity; ensuring solvency by regulating the size and structure of property and capital of the enterprise; ensuring liquidity of assets. Despite numerous publications on housing reform and management of housing and communal enterprise in Ukraine, there is virtually no research in academic practice that aims to consider the reasons for the low quality of services in this area. Improving the competitiveness of Municipal Enterprises can substantiate strategic priorities for  their reforming and development. The conducted study aims to reveal these issues.
Keywords: housing and communal enterprise; improvement of communal enterprise activity; development